Unraveling the Gender Gap: A Comparative Analysis of School Enrollment and Secondary Education Completion in Pakistan's Provinces - REHMAN, Nadia; ANDLEEB, Irum; IQBAL, Mussarat (Journal of Research in Educational Sciences, 2023)
This study examines the gender gap in school enrollment and secondary school completion in Pakistan using secondary data from the Pakistan Social and Living Standards Measurement Survey (PSLM) and Pakistan Education Statistics reports. A comparative analysis of the four provinces and their districts is conducted to identify regional dynamics contributing to gender disparities in education. The research investigates the relationship between students who ever attended school, those who passed secondary school, and the gender gap in enrollment. Descriptive statistics analyze school enrollment rates and dropouts across different regions. Data from the official governmental reports, including the Pakistan Bureau of Statistics and PSLM (2019-20), and education statistics reports from 2017 for Punjab, Sindh, Khyber Pakhtunkhwa, and Balochistan, serve as the foundation for this analysis. The study offers valuable insights into the complex web of causality and influence shaping the persistence of gender disparities in education in Pakistan.